Pulpwood plantations as carbon sinks in Indonesia: methodological challenge and impact on livelihoods - Pirard, R. (Center for International Forestry Research, 2005)
The Clean Development Mechanism (CDM) was created under the Kyoto Protocol, in order to help industrialized countries achieve their Greenhouse Gas (GHG) emission reduction targets at a lower cost. A second objective of the CDM is to help developing countries achieve sustainable development. To become eligible these projects have to demonstrate their additionality, and have a positive impact on local communities’ livelihoods. But the methodologies that have been proposed seem unsatisfactory, and the social impacts are often debated. This paper provides new insights on these methodologies, their weaknesses and potential improvements, and explores the social impacts of an afforestation/reforestation CDM activity with a high carbon sequestration potential. We studied a large-scale pulpwood plantation in Indonesia, which is perceived as a way to sequestrate great quantities of carbon in a short time, and as an alternative to natural forest supplies for the domestic pulp industry. We collected complete data on the establishment and production costs, and the carbon sequestration potential. We also took advantage of our ongoing research on the Indonesian Pulp & Paper (P&P) sector to interpret these results, and evaluate the relevance of widely used and proposed methodologies for additionality assessment. Finally, research on site allowed us to obtain data on the plantation’s impact on the people living nearby. According to our research, fast-growing tree plantations face production costs far higher than revenues gained from the sale of carbon credits, even with a relatively important carbon sequestration. But calculations made according to usual methodologies can be misleading. We show that context analysis is more relevant, and that profitability calculations lead to wrong conclusions. From a social point of view, pulpwood plantation projects could increase livelihoods in the short term, but this depends very much on the opportunities for locals to combine employment in the plantation with land uses generating higher incomes per hectare.